Modelling the long-term mass balance and firn evolution of glaciers around Kongsfjorden, Svalbard. Issue 228 (2015) - Pelt, Ward Van; Kohler, Jack
Abstract: We analyse the long-term (1961–2012) distributed surface mass balance and firn evolution of the Kongsvegen and Holtedahlfonna glacier systems in northwestern Svalbard. We couple a surface energy-balance model to a firn model, with forcing provided from regional climate model output. In situ observational data are used to calibrate model parameters and validate the output. The simulated area-averaged surface mass balance for 1961–2012 is slightly positive (0.08 mw.e.a −1 ), which only fractionally compensates for mass loss by calving. Refreezing of percolating water in spring/summer (0.13 m w.e. a −1 ) and stored water in fall/winter (0.18 m w.e. a −1 ) provides a buffer for runoff. Internal accumulation, i.e. refreezing below the previous year's summer surface in the accumulation zone, peaks up to 0.22 m w.e. a −1, and is unaccounted for by stake observations. Superimposed ice formation in the lower accumulation zone ranges as high as 0.25 m w.e. a −1 . A comparison of the periods 1961–99 and 2000–12 reveals 21% higher annual melt rates since 2000 and a 31% increase in runoff, which can only in part be ascribed to recent warmer and drier conditions. In response to firn line retreat, both albedo lowering (snow/ice–albedo feedback) and lower refreezing rates (refreezing feedback) further amplified runoff.